Single‐Cell Analysis of Endothelial Cell Injury in IgA Nephropathy - Yong‐Chang Yang; Lin Zhu; Jing‐Ying Zhao; Bo Zhang; Xiao‐Meng Wang; Wai W. Cheung; Cheng‐Guang Zhao; Ping Zhou (Immunity, Inflammation and Disease)
ABSTRACT Background The precise mechanisms responsible for renal injury in IgA nephropathy (IgAN) are not fully understood. Our study employed an extensive scRNA‐seq analysis of kidney biopsies obtained from individuals with IgAN, with a specific emphasis on investigating the involvement of renal endothelial cells. Methods We obtained data from the Gene Expression Omnibus database and conducted bioinformatics analysis, which included enrichment analysis of differentially expressed genes, AUCell analysis, and high‐dimensional weighted gene co‐expression network analysis (hdWGCNA). The results of these analyses were further validated using human renal glomerular endothelial cells (HRGECs). Results The ScRNA‐seq data uncovered notable variations in gene expression between IgAN and control kidney tissues. The enrichment analysis using AUCell demonstrated a high presence of adhesion molecules and components related to the mitogen‐activated protein kinase signaling pathway within the renal endothelial cells. Furthermore, through hdWGCNA analysis, it was discovered that interleukin (IL)‐6, Rac1, and cadherin exhibited associations with the renal endothelial cells. Stimulation of HRGECs with IL‐6/IL‐6 receptor resulted in a significant reduction in VE‐cad expression while inhibiting Rac1 led to a substantial decrease in Rac1‐GTP levels and an increase in VE‐cad expression. Conclusion This study presents novel findings regarding the contribution of renal endothelial cells to the development of IgAN, as it demonstrates that IL‐6 negatively regulates VE‐cad expression in HRGECs via Rac1. These results highlight the significant involvement of renal endothelial cells in the pathogenesis of IgAN.